Competitive Debate as Innovation in Gamification and Training for Adult Learners: A Conceptual Analysis - Sánchez Prieto, Guillermo A.; Martín Rodrigo, María José; Rua Vieites, Antonio (Frontiers in Psychology, 2021)
Adult learners demand teaching innovations faster and more attractive. In response to those demands and skill training challenges this work presents a conceptual analysis, introducing the strengths of competitive debate as an impact training model within the frame of gamification. There is a research gap about debate as a game, and/or training technique almost unexplored in continuous training. Through a literature review around the concepts of game, game experience and gamification, definitions, and characteristics of each one it is concluded that with no doubt competitive debate is an ideal gamification instrument for a high impact training.